2016
DOI: 10.1111/oik.03455
|View full text |Cite
|
Sign up to set email alerts
|

To recycle or steal? Nutrient resorption in Australian and Brazilian mistletoes from three low‐phosphorus sites

Abstract: Resorption is the process by which nutrients are withdrawn from leaves prior to leaf fall. Mistletoes are generally thought not to rely on nutrient resorption; being xylem-tapping parasites, they instead derive the nutrients required for new growth from their host plant, at little or no cost. We measured nutrient (N, P, K, Ca, Mg) resorption in 18 parasitic mistletoe-host species pairs distributed across three sites with notably low-P soil, also quantifying relationships with leaf lifespan (LL) and specific le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 44 publications
1
12
0
Order By: Relevance
“…Mistletoes from the Loranthaceae family have been shown to be very inefficient in resource use, which is proposed to be a consequence of their unique life form (Scalon and Wright 2015;Scalon et al 2016b). The patterns found for the Santalaceae mistletoe studied here were similar, suggesting that mistletoe leaf traits could be constrained by the life form, or even by evolutionary aspects, because the group formed by Santalaceae-Opiliaceae is a sister group of Loranthaceae (Der and Nickrent 2008).…”
Section: Mistletoe and Host Differencessupporting
confidence: 51%
“…Mistletoes from the Loranthaceae family have been shown to be very inefficient in resource use, which is proposed to be a consequence of their unique life form (Scalon and Wright 2015;Scalon et al 2016b). The patterns found for the Santalaceae mistletoe studied here were similar, suggesting that mistletoe leaf traits could be constrained by the life form, or even by evolutionary aspects, because the group formed by Santalaceae-Opiliaceae is a sister group of Loranthaceae (Der and Nickrent 2008).…”
Section: Mistletoe and Host Differencessupporting
confidence: 51%
“…Based on the theoretical model of Wright and Westoby (2003), under low fertility conditions, the energetic costs of resorbing nutrients from senescing leaves were lower than that of uptaking nutrients directly from the soil. From a cost-benefit perspective, our results suggested that the costs of resorption relative to uptake from soils were less for Q. variabilis at the P-deficient site (Scalon et al 2017). For this study, the two P-type sites were similar in climatic conditions, but different in soil P concentrations.…”
Section: Discussionmentioning
confidence: 73%
“…Thus, at the P-rich site, the energy cost of acquiring nutrients from the soil should be far lower than resorbing them from senescing leaves; thus, Q. variabilis reduced P resorption, particularly P resorption proficiency. In comparison, at the P-deficient site, the cost of Table 4 Partial R 2 calculated for the generalized linear models showing the effects of C, N, and P concentrations in green leaves and soils on the C:N, N:P, and C:P resorption efficiency ratios, log e (C RE /N RE ), log e (N RE / P RE ), and log e (C RE /P RE ), at P-rich and P-deficient sites, in subtropical China nutrient uptake from soils might be more expensive than nutrient resorption from senescing leaves; therefore, Q. variabilis had a higher P resorption, especially the higher P resorption proficiency (Wright and Westoby 2003;Kobe et al 2005;Scalon et al 2017). Moreover, species growing in diverse nutritional conditions can develop nutrient-based ecotypes (populations) (Kawecki and Ebert 2004;Savolainen et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…We add to this by demonstrating the root hemiparasite E. cupressiformis also has high levels of K in senesced leaves, and had the highest levels of P in the community. Hemiparasitic plants are important contributors to soil nutrient cycles in ecosystems around the world, through litterfall rich in nutrients such as K and P ( Quested et al 2003 ; March and Watson 2010 ; Ndagurwa et al 2014 ; Scalon et al 2017 ). Litterfall from hemiparasitic species has positive effects on community productivity ( March and Watson 2007 ; Spasojevic and Suding 2011 ; Fisher et al 2013 ) and bottom-up effects on diversity ( Watson 2002 ), leading some to describe them as a keystone resource ( Watson and Herring 2012 ).…”
Section: Discussionmentioning
confidence: 99%